The Role of Agricultural Credit, Extension Services, and Regional Policies on the Growth of the Food Crop Sub-sector in Pacitan Regency: A Three-Stage Least Squares Simultaneous Model Approach - Adi Budiwan; Syarif Imam Hidayat; Sri Tjondro Winarno; Nuriah Yuliati (Postgraduate, University of Mataram, 2026)
This study examines the determinants of stagnant growth in the food crop subsector in Pacitan Regency despite extensive government support policies. Using annual time-series data from 2004–2024, a simultaneous equation model estimated by Three-Stage Least Squares (3SLS) is employed to capture the interaction between agricultural credit, extension services, and regional policies. The results show that agricultural extension has the largest and most significant elasticity with respect to food crop output, followed by fertiliser subsidies, while agricultural credit exhibits a positive but relatively small elasticity due to its limited use for productive investment. Policy simulation results indicate that a 20% increase in extension services generates the strongest impact on output growth and poverty reduction, whereas credit expansion alone produces only a moderate effect. The combined policy scenario—integrating extension strengthening, fertiliser subsidies, and credit reform—yields the highest synergistic gains in production and welfare. These findings provide empirical evidence that institutional complementarity is crucial for enhancing agricultural productivity in marginal regions and offer a data-driven framework for designing integrated regional agricultural policies